2023
DOI: 10.3390/bs13070585
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Studies Supporting Metaphorical Embodiment

Omid Khatin-Zadeh,
Danyal Farsani,
Jiehui Hu
et al.

Abstract: This paper presents a review of studies that have provided evidence supporting metaphorical embodiment. These studies are divided into three categories of behavioral, neuroimaging, and corpus studies. After summing up the findings of these studies, it is concluded that metaphorical embodiment is supported by these three lines of research. This is followed by a review of a number of studies that have measured sensorimotor and action effector strengths of various concepts. Then, the idea of sensorimotor and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…There is significant empirical support for embodied metaphor theory, coming from action-sentence compatibility studies, eye-tracking studies, hand-prime studies, gesture-inlearning studies, and neuroimaging studies on sensorimotor activation during metaphor processing and mental imagery processing [39]. As mentioned, this literature supports the idea that even abstract, complex metaphors are compositions of simpler metaphors.…”
Section: Embodied Cognitionmentioning
confidence: 68%
See 2 more Smart Citations
“…There is significant empirical support for embodied metaphor theory, coming from action-sentence compatibility studies, eye-tracking studies, hand-prime studies, gesture-inlearning studies, and neuroimaging studies on sensorimotor activation during metaphor processing and mental imagery processing [39]. As mentioned, this literature supports the idea that even abstract, complex metaphors are compositions of simpler metaphors.…”
Section: Embodied Cognitionmentioning
confidence: 68%
“…The fundamentally metaphorical nature of thought in general, and spontaneous thought in particular, is a central finding of embodied cognition research. Rather than view all cognition as disembodied sign manipulations emerging solely in response to verbal instruction or cultural observation, cognitive linguists challenged the older cognitive paradigm using a number of crucial observations of real-world, everyday language [1,16,39]. The literature of embodied cognition and cognitive linguistics, in fact, shows that much of our thought can be described not in meaningless signs but in terms of embodied metaphors, which are themselves defined as: "frame-to-frame mappings across conceptual domains.…”
Section: Embodied Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than view all cognition as disembodied sign manipulations, cognitive linguists challenged the classic paradigm. They did so using a number of crucial observations of realworld, everyday language (reviewed in Lakoff, 2012; see also Lakoff & Johnson, 1980, 1999and Khatin-Zadeh et al, 2023, for example, the way basic level categories and spatial relations across many languages require universal primitives that reference the human body (Langacker, 2008).…”
Section: Embodied Cognitionmentioning
confidence: 99%
“…Recently, a growing body of studies have investigated the question of the embodiment of action metaphor processing by comparing metaphoric action sentences with non-metaphoric ones, and yielded mixed findings (for an overview, see Khatin-Zadeh et al, 2023 ). Some of the studies have demonstrated the activation of the sensorimotor systems during action metaphor comprehensions ( Desai et al, 2011 , 2013 ; Boulenger et al, 2012 ; Lauro et al, 2013 ; Schuil et al, 2013 ; Fernandino et al, 2016 ; Martin, 2016 ; Johari et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%